Circumferential Type A Aortic Dissection and Intimal Intussusception of the Aorta Causing Severe Aortic Regurgitation and Obstruction of the Left Main Coronary Artery. Issue 3 (10th December 2012) - Yang, Eric H.; Kwon, Murray H.; Mahajan, Aman; Child, John S.; Tobis, Jonathan M.; Manthripragada, Gopi; Silverstein, Cheri A.; Shamsa, Kamran
Mini‐Abstract Circumferential dissection of the ascending aorta is a rare subtype of Type A aortic dissection which involves the entire intimal layer of the aorta which can cause a variety of devastating sequelae, given its propensity to involve the aortic valve and coronary arteries. Echocardiography is essential in making the diagnosis and visualize its involvement of the cardiovascular system, as invasive aortography can be limited in visualization of this unusual variant of aortic dissection. We present a patient who suffered a circumferential dissection of the ascending aorta which also caused severe aortic regurgitation and ischemia from left main coronary artery obstruction.